2016
DOI: 10.1111/1742-6723.12602
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for patients presenting to an emergency department with back pain: Impact on patient pathway

Abstract: This study provides benchmark data on the use of imaging for back pain in an Australian ED, an area which has been largely unexplored. The rate of imaging in the ED was higher than previously reported in a General Practice setting. Consistent with guidelines, patients older than 70 were more than twice as likely to receive imaging compared to younger patients. It was beyond the scope of the current study to determine whether these images were clinically indicated and further research is required to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 17 publications
5
36
1
Order By: Relevance
“…In one US ED study, for instance, opioids were prescribed to 62% of patients with low back pain . The proportion of patients with low back pain receiving imaging is also high: 31% are estimated to be imaged in the Australian ED . Much of the imaging is not indicated, considering the low prevalence of serious pathologies in patients with low back pain .…”
Section: Usual Care For Non‐serious Low Back Pain In the Emergency Dementioning
confidence: 99%
See 1 more Smart Citation
“…In one US ED study, for instance, opioids were prescribed to 62% of patients with low back pain . The proportion of patients with low back pain receiving imaging is also high: 31% are estimated to be imaged in the Australian ED . Much of the imaging is not indicated, considering the low prevalence of serious pathologies in patients with low back pain .…”
Section: Usual Care For Non‐serious Low Back Pain In the Emergency Dementioning
confidence: 99%
“…Furthermore, rates of inpatient admission (that is, for further investigation and monitoring) are higher than expected if guidelines were followed. For example, 34% of low back pain ED presentations led the patient to being admitted to an Australian hospital . However, the majority of those admitted (59%) were diagnosed as having non‐surgical spinal disorders, which guidelines suggest are best treated in primary care …”
Section: Usual Care For Non‐serious Low Back Pain In the Emergency Dementioning
confidence: 99%
“…From these presentations, 43.8% were categorised as having ‘muscular’ LBP, and 17.1% of these patients were admitted with an average length of stay at 6.4 days . More recent data from an Australian metropolitan hospital has reported higher prevalence, with 2.2% of all presentations in 2013 being due to LBP, and 32.2% of these patients being admitted . Hospital admission accounts for significantly greater expenditure, estimated at 47.6% ($560 million) of the total healthcare expenditure on LBP .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these guidelines, American data from the past decade indicates there has been a three‐fold increase in the use of advanced imaging techniques (both magnetic resonance imaging and computed tomography, up to 11.3%), with stable use of radiographs (17%), and an increase in prescription opioid use (29.1%, up to 61% at discharge) in place of simple analgesics . In Australia, the available data also suggest high rates of imaging in ED, with radiography requested for 26.2% of patients and advanced imaging requested for 5.6% of patients . These approaches offer no improvements to patient outcomes, increase exposure to the risks of opioid medications use and unnecessary radiation and lead to increases in the economic burden of LBP …”
Section: Introductionmentioning
confidence: 99%
“…In one study, only 30% of patients underwent imaging tests and most were performed in the elderly patients over 70 years of age, one-third of the patients who were admitted to the hospital reported that the imaging test they received did not have a direct relationship with their symptoms or the necessity of hospitalization, and reported that we should reduce the number of imaging tests in the future [6]. Our study also showed that patients over 65 years of age had a higher proportion in the group exceeding 3 hours, and more imaging tests were performed on them.…”
Section: Discussionmentioning
confidence: 99%